OCCURRENCE OF THE BACTERIA IN A HOSPITAL ENVIRONMENT AND THEIR SENSITIVITY PROFILE TO THE MAIN ANTIMICROBIALS IN A REFERENCE GENERAL HOSPITAL IN CURITIBA, BRAZIL - Kloss, Camila Padilha; Abdullah, Nicole; Erdmann, Oona Salomão; Borges, Beatriz Essenfelder; de Macedo, Viviane (Arquivos de Ciências da Saúde da UNIPAR, 2023)
Introduction: Antimicrobial resistance rates are increasing in both hospital and community settings, creating a favorable environment for the development of superbacteria. Therefore, local studies are necessary for the proper management of current antimicrobial arsenals and for addressing the current bacteriological scenario. Aim: The aim of this study is to profile bacterial epidemiology in a hospital in Curitiba, Brazil and associate it with the effectiveness of antimicrobial therapy. Methodology: Data from 2019 to 2021 were collected by the Center for Epidemiology and Hospital Infection Control (CEHIC), and this was a quantitative single-center study. Results: The most commonly detected microorganisms were Escherichia coli, Staphylococcus aureus, Klebsiella pneumoniae, Staphylococcus epidermidis, Pseudomonas aeruginosa, Enterococcus faecalis, Acinetobacter baumannii, Staphylococcus haemolyticus, Staphylococcus hominis, and Enterobacter cloacae. A. baumannii and K. pneumoniae had the lowest mean sensitivity coefficients, while S. aureus was the most sensitive. Erythromycin was the least effective antimicrobial agent, while daptomycin was the most effective. Conclusion: These results are consistent with the literature and can be used to optimize empiric therapies, as there are already important therapeutic failures associated with antimicrobial resistance.